Association of high-sensitivity cardiac troponin T with mortality and cardiovascular events in a community-based prospective study in Beijing. Issue 6 (26th June 2017) - Xiao, Wenkai; Cao, Ruihua; Liu, Yuan; Wang, Fan; Bai, Yongyi; Wu, Hongmei; Ye, Ping
Abstract : Objective: The prognostic value of cardiac troponins in apparently healthy populations is not well established. The aim of this study was to investigate the prognostic properties of high-sensitivity cardiac troponin T (hs-cTnT) for long-term adverse outcomes. Setting: A community-dwelling prospective survey of residents from two communities in Beijing. Participants: From September 2007 to January 2009, 1680 participants were initially enrolled. Of these, 1499 (870 females, mean age: 61.4 years) participants completed the survey and were followed up for a median of 4.8 years (IQR: 4.5–5.2). Outcome measures: The primary outcome was the occurrence of all-cause mortality and major cardiovascular events. Results: Overall, 820 individuals (54.7%) had detectable hs-cTnT levels. During the follow-up, 52 participants (3.5%) died, 154 (10.3%) had major cardiovascular events and 99 (6.6%) experienced new-onset coronary events. Compared with those with undetectable hs-cTnT levels, participants with hs-cTnT levels in the highest category (≥14 ng/L) had a significantly increased risk for all-cause mortality (adjusted HR (aHR): 2.07, 95% CI 1.05 to 3.01), major cardiovascular events (aHR: 3.27, 95% CI 1.88 to 5.70) and coronary events (aHR: 4.50, 95% CI 2.26 to 9.02) in covariate-adjusted analyses. No differences in stroke incidence were found (aHR: 1.27, 95% CI 0.69 to 2.62). Also, significant associations were presented when hs-cTnT levels were modelled as a continuous variable and when analysing changes in hs-cTnT levels over time with adverse outcomes. The addition of troponin T levels to clinical variables led to significant increases in risk prediction with a marked improvement in the C-statistics (p=0.003 or lower). Conclusions: In this cohort of individuals from a community-based population, cTnT levels measured with a highly sensitive assay were associated with increases in the subsequent risk for all-cause mortality and major cardiovascular events. These results might support screening for at-risk individuals.